2018
DOI: 10.21608/ejm.2018.3833.1082
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activities of endophytic fungi of Red Sea aquatic plant Avicennia marina

Abstract: M EDICINal plants endophytes are a promising trend to meet the increasing threat of drug-resistant strains of human pathogens. Mangrove plants (Avicennia marina) have been used in folklore medicines where extracts from mangrove species have proven inhibitory activity against human, animal and plant pathogens. This study focuses particularly on testing the antimicrobial activity of mangrove endophytic fungi isolated from South Safaga and Wadi abu Hamrah mangrove along the Red Sea against different human pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…Endophytic fungi are considered a reservoir of active biochemical compounds such as phenols, alkaloids, steroids, peptides, terpenoids, isocoumarins, quinones, phenylpropanoids, lignans, lactones, flavonoids and others (Tan and Zou 2001;Radić andŠtrukelj 2012;Bedi et al 2018;Eid et al 2019;Khalil et al 2019), which are used for multiple applications such as antibiotics, agrochemicals, immunosuppressants, antiparasitic, antioxidants, antibacterial, antiviral, antifungal, anti-inflammatory and anticancer agents (Gunatilaka 2006;Hussain et al 2014;Meena et al 2017). Secondary metabolites of endophytic fungi from mangrove plants have a biological activities including antimicrobial (Ling et al 2016;Basheer et al 2018), antioxidant (Ravindran et al 2012;Gunasekaran et al 2017;Yang et al 2018) and anticancer (Elavarasi et al 2012;Chokpaiboon et al 2016) activities. Recently, Bibi et al (2020) reported that mangrove endophytic fungi are good producers of bioactive secondary metabolites with promising biological activities including anticancer, antimicrobial and antioxidant.…”
Section: Introductionmentioning
confidence: 99%
“…Endophytic fungi are considered a reservoir of active biochemical compounds such as phenols, alkaloids, steroids, peptides, terpenoids, isocoumarins, quinones, phenylpropanoids, lignans, lactones, flavonoids and others (Tan and Zou 2001;Radić andŠtrukelj 2012;Bedi et al 2018;Eid et al 2019;Khalil et al 2019), which are used for multiple applications such as antibiotics, agrochemicals, immunosuppressants, antiparasitic, antioxidants, antibacterial, antiviral, antifungal, anti-inflammatory and anticancer agents (Gunatilaka 2006;Hussain et al 2014;Meena et al 2017). Secondary metabolites of endophytic fungi from mangrove plants have a biological activities including antimicrobial (Ling et al 2016;Basheer et al 2018), antioxidant (Ravindran et al 2012;Gunasekaran et al 2017;Yang et al 2018) and anticancer (Elavarasi et al 2012;Chokpaiboon et al 2016) activities. Recently, Bibi et al (2020) reported that mangrove endophytic fungi are good producers of bioactive secondary metabolites with promising biological activities including anticancer, antimicrobial and antioxidant.…”
Section: Introductionmentioning
confidence: 99%
“…El-Maghraby et al (2013) has explored three leguminous plant roots for Endophytic fungi in Egypt. Basheer et al (2018) isolated the endophytic fungi from Avicennia marina and investigated the antibacterial and antifungal properties of their crude extracts against some important human pathogens. Plant growth-promoting activities for bacterial and fungal endophytes isolated from Teucrium polium L. were investigated by Saad El-Din Hassan (2017).…”
Section: Introductionmentioning
confidence: 99%
“…Fungal endophytes have already been reported in Avicennia alba (Lee et al, 2019) and in A. marina (Bhimba et al, 2012;Basheer et al, 2018;Bibi et al, 2020). Penicillium citrinum was reported in the latter (Liu J. et al, 2015).…”
Section: Discussionmentioning
confidence: 91%